(untitled) (International conference on multidisciplinary science, 2023)
The article for "Training athletes physically and psychologically" provides a concise overview of the topic, emphasizing the integrated approach to athlete development. It highlights the significance of combining physical training with psychological strategies to optimize performance, enhance resilience, and contribute to the holistic well-being of athletes.